2006
DOI: 10.1139/b05-147
|View full text |Cite
|
Sign up to set email alerts
|

Freezing in nonacclimated oat: thermal response and histological observations of crowns during recovery

Abstract: The complex nature of freezing in plants may be easier to understand if freezing is studied in nonacclimated plants at temperatures just below freezing. Thermal patterns of model systems frozen at –2.6 °C were compared with those of crown tissue from oat ( Avena sativa L.). Thermal patterns of live crowns more closely resembled those of fructan and sugar solutions with filter paper than of plain water or a BSA solution. When the percentage of water freezing in nonacclimated plants at –2.6 °C was manually limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Histological observations and evaluation of internal tissues, either during freezing or shortly after thawing have been conducted to determine the freezing tolerance of various tissues (Aloni and Griffith 1991 ; Livingston et al 2005 ; 2006 , 2013 ; Olien and Marchetti 1976 ; Pearce et al 1998 ; Stier et al 2003 ; Tanino and McKersie 1985 ; Zamecnik et al 1994 ). However, the size of tissues that need to be examined, and the fact that they are embedded in and surrounded by other plant structures, have made the interior of the plant difficult if not impossible to monitor during freezing.…”
Section: Introductionmentioning
confidence: 99%
“…Histological observations and evaluation of internal tissues, either during freezing or shortly after thawing have been conducted to determine the freezing tolerance of various tissues (Aloni and Griffith 1991 ; Livingston et al 2005 ; 2006 , 2013 ; Olien and Marchetti 1976 ; Pearce et al 1998 ; Stier et al 2003 ; Tanino and McKersie 1985 ; Zamecnik et al 1994 ). However, the size of tissues that need to be examined, and the fact that they are embedded in and surrounded by other plant structures, have made the interior of the plant difficult if not impossible to monitor during freezing.…”
Section: Introductionmentioning
confidence: 99%
“…Complicating research on cold acclimation is evidence that certain tissues in the below-ground portion of the stem called the crown, acclimate to a different extent than others [7], [8]. For that reason, it is not uncommon for leaves and roots to die from freezing injury but, during recovery an intact plant grows out of surviving tissues within the crown.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous genes have been found to be related to cold acclimation [6], [9], [10], [11], [12], [13]. The expression of some genes in wheat and barley have been localized to the vascular transition zone [14], [15] which is also the region of the crown that is most freezing tolerant [7], [8]. It has been suggested that the expression of other genes are associated with structural changes that occur in crown tissue [8], [16], [17] such as the increase in lignified cells and the development of a barrier between roots and internal crown tissue [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…However, Canny (1995) demonstrated that the solute concentration in the apoplast is not uniform but that solutes tend to accumulate in discrete regions termed sumps. Livingston et al (2005Livingston et al ( , 2006b found regions of oat crowns recovering from freezing that appeared to be barriers to freeze damage that could be evidence of the sumps to which Canny (1995) refers. In addition to sugars being distributed unevenly in the apoplast and in separate regions of the crown, the layer of liquid water into which sugars have apparently been released would be very small due to the presence of apoplastic ice at ÿ3 8C (Gusta and Fowler, 1977;Single and Marcellos, 1981;Pearce and Ashworth, 1992).…”
Section: Introductionmentioning
confidence: 99%